Tuberculosis of the Breast: A Case Report (TAJ: Journal of Teachers Association, 2009)
A middle aged woman presented with a lump and discharging sinus in her breast. On first look, the lesion seemed to be a carcinoma of breast. The patient got enlarged axillary lymph nodes with fever in the evening, night sweating and loss of weight, indicating the lesion to be of tuberculous in origin. FNAC indicated the lesion to be tuberculous but open biopsy was advised by the pathologist for confirmation. Excision biopsy of the lesion confirmed the lesion as tuberculous. Treatment with anti-tuberculous drugs cured the disease. A lump in the breast with skin involvemennt and axillary lymph node enlargement may be considered a malignant tumour on first sight, but tuberculosis cannot be ruled out, especially if a sinus is present along with systemic manifestations of the disease. doi: 10.3329/taj.v21i1.3224 TAJ 2008; 21(1): 73-76